2022
DOI: 10.1155/2022/5916379
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Ultrasonographic Appearance of Papillary Thyroid Microcarcinoma and BRAF V600E Mutation

Abstract: The study was conducted to investigate the correlation between the ultrasonographic appearance of a thyroid nodule and the BRAF V600E mutation. Patients with thyroid nodules ( n = 186 ), for which BRAF V600E testing and cytopathology analysis were performed, and who underwent subsequent surgery for nodule resection were enrolled in this study. For each patient, color Doppler ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
1
1
1
Order By: Relevance
“…Surprisingly, the positive BRAF V600E mutation was increased in older patients in benign cytology and in the nodules classi ed both TI-RADS 4a and TBSRTC II. Several US features, such as the presence of microcalci cations, marked hypoechogenicity, irregular margins have been reported to predict malignancy [37,38], and were associated with BRAF V600E mutation in thyroid nodules [39]. However, in our study, the US features mentioned above had no signi cant difference between positive and negative BRAF V600E mutation.…”
Section: Discussioncontrasting
confidence: 68%
“…Surprisingly, the positive BRAF V600E mutation was increased in older patients in benign cytology and in the nodules classi ed both TI-RADS 4a and TBSRTC II. Several US features, such as the presence of microcalci cations, marked hypoechogenicity, irregular margins have been reported to predict malignancy [37,38], and were associated with BRAF V600E mutation in thyroid nodules [39]. However, in our study, the US features mentioned above had no signi cant difference between positive and negative BRAF V600E mutation.…”
Section: Discussioncontrasting
confidence: 68%
“…17 Several US features, such as microcalcification, marked hypoechogenicity and irregular margins were more frequently observed in thyroid nodules harbouring positive BRAF V600E mutation than negative BRAF V600E mutation. 30,39 In our study, there were no significant differences in C-TIRADS classification, along with US features between positive and negative BRAF V600E mutation in benign cytologic results. The reason may be that the majority of cases were classified as 3-4a, so the result of C-TIRADS classification was not referential.…”
Section: Discussionmentioning
confidence: 45%
“… 32 Experimental findings indicate that BRAF V600E-mutated thyroid cancers display higher regional cervical lymph node metastases rates than non-mutated ones, suggesting a strong correlation with thyroid carcinogenesis, extraperitoneal cancer spread, recurrence, and lymph node metastases, echoing prior research. 33 , 34 This information aids surgeons in determining appropriate surgical strategies during initial procedures. 35 , 36 Nucera et al’s experiments demonstrated that PLX4720, a specific BRAF V600E inhibitor, suppresses BRAF V600E thyroid cancer cell migration and invasion, thereby reducing tumor aggression.…”
Section: Discussionmentioning
confidence: 99%